New Fragments of Papyrus Berlin 3024: The Missing Beginning of the Debate between a Man and his Ba and the Continuation of the Tale of the Herdsman (P. Mallorca I and II) - Escolano-Poveda, Marina (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
P. Mallorca I and II are identified as part of the lost sections of P. Berlin 3024, belonging to the lost beginning of The Debate between a Man and His Ba, and to the lost sections of The Tale of the Herdsman. A detailed material analysis is done, and a hypothesis for the origin of the fragments is discussed, in connection to P. Amherst III. The edition of the text is presented, together with a tentative reconstruction of P. Berlin 3024 + P. Amherst III + P. Mallorca II. Finally, a new interpretation of both the Debate and the Herdsman is proposed, based on a re-examination of the contents of both texts in connection with the new data provided by P. Mallorca I and II.